CARACTERÍSTICAS PSICOSSOCIAIS E DE PERSONALIDADE DE ADOLESCENTES INFRATORES EM CUMPRIMENTO DE MEDIDA SOCIOEDUCATIVA - MACEDO, VALÉRIA GOUVEIA DE (2016)
To achieve the proposed objectives, ie up and describe sociocultural indicators of a sample of adolescents in compliance with socio-educational measures, and describe psychological characteristics and personality of juvenile offenders, the study surveyed 47 adolescents in compliance with socio-educational measures. There were two stages of work: first, the 47 teens participated in a semistructured interview; in the second, ten of these adolescents were selected and submitted to a projective tool to research aspects of personality: the "Drawing the Human Figure" of Machower, adapted by Van Kolck (1956; 1984). The theoretical discussion of the results was based on a post-Freudian psychoanalytic approach to understanding both adolescence as a phase of human development as the antisocial behavior. The study results confirmed the arising theory of psychological literature that addresses common patterns during adolescence, a phase in which there is a complex of individual factors of biological maturity associated with social / cultural environment and, in turn, establish relations with the psychological or mental bodies of the subject along with the specific characteristics of each individual. In search of understanding of these common sample of adolescent offenders used in this study patterns, psychosocial, cultural and demographic data were collected; psychosocial aspects and psychodynamic aspects and personality characteristics. In conclusion, the study highlighted the adolescent problematic in conflict with the law, associated with social, mental health, and the psychic development, signaling the need for focused Psychoprophylactic actions for child population, young family groups and the community representing its surroundings